Symmetrifying Smart Home - Sungyong Ahn (Media Theory)
This paper investigates how the current domestic application of the Internet of Things (IoT), called “smart home,” changes the socio-phenomenological meaning of place-making. It describes a smart home as a topological continuum that could unfold lots of functional spaces—those optimized for a variety of predictable user behaviors and intentions, such as going to bed, working out, and energy-saving—according to how software applications redeploy its embedded sensors and actuators into certain algorithmic orders. This continuum once buried under people’s daily routines is constantly re-excavated in a smart home and re-differentiated into the new service domains of the IoT. This paper develops a topological framework to analyze the new form of media power behind this perpetual place-binding of smart spaces, which I term topological power. For this goal, it borrows Bernhard Riemann and Henri Poincaré’s mathematical thinking of manifold, or multiplicity, beneath the geometric structure of space.